Strategy + teamwork = great products : management techniques for manufacturing companies - Parker, Frederick (Productivity Press, 2014)
Role of the Board of DirectorsRole of the CEOArt of PromotionArt of Demotion or FiringHow to Survive as a CEOTen Commandments for the CEOCreating the Business PlanStrategic PlanImportance of the Right StrategyCreating the Business PlanCorporate CultureDeliver on Your PromisesDiscipline in the OrganizationClose SupervisionChain of CommandResponsivenessAttainable GoalsMission StatementSpan of ControlFlat OrganizationFlexibilitySummary of Corporate CultureCommunicationsOrganization of Large CorporationsManufacturing StrategiesOutsourcing and Make or Buy StrategiesCapital ExpendituresManufacturing.